Safety and immunogenicity of high doses of quadrivalent influenza vaccine in children 6 months through <18 years of age: A randomized controlled phase II dose-finding trial. Issue 11 (12th March 2021) - Chang, Lee-Jah; Anderson, Evan J.; Jeanfreau, Robert; He, Ying; Hicks, Bryony; Shrestha, Anju; Pandey, Aseem; Landolfi, Victoria; DeBruijn, Iris; ,
Highlights: Safety and immunogenicity of IIV4-HD was evaluated in USA and Canadian children 6 mos.-17 yrs. of age. Three dose formulations of IIV4-HD (30 45, and 60 µg HA/strain/dose) were safe and well tolerated. IIV4-HD 60 µg HA/strain/dose formulation generated higher immunogenicity compared to IIV4-SD. Highest GMT ratios seen in children 6–35 months of age who received IIV4-HD (60 µg HA/strain/dose) Abstract: Quadrivalent high-dose inactivated influenza vaccine (Fluzone® High-Dose Quadrivalent, IIV4-HD) was licensed in the USA in 2019 for adults ≥ 65 years of age. This Phase II study examined safety and immunogenicity of 3 dose formulations of IIV4-HD in healthy children. In a randomized, modified double-blind, active-controlled trial in the USA and Canada, 661 children aged 6 months through < 18 years received 1 or 2 doses intramuscularly of standard-dose quadrivalent influenza vaccine (IIV4-SD; 15 µg HA/strain), IIV4-HD at 3 dose levels (30, 45, and 60 µg HA/strain), or adjuvanted trivalent influenza vaccine (aIIV3, 7.5 µg HA/strain). Rates of unsolicited AEs were similar irrespective of dose. No treatment-related serious adverse events or deaths were reported. Reactogenicity was slightly higher for IIV4-HD than IIV4-SD, although most solicited reactions were grade 1 or 2. Hemagglutination inhibition (HAI) and seroneutralization antibody titers were measured 28–35 days after each dose. Geometric mean HAI titers increased with increasing hemagglutinin dose, especially in children 6 months through < 3 years. For IIV4-HD 60 µg, in participants 6 months through < 18 years of age, the geometric mean titer ratio (95% confidence interval) versus IIV4-SD was 1.35 (0.94, 1.94) for A/H1N1, 2.51 (1.77, 3.55) for A/H3N2, 1.60 (1.17, 2.18) for B/Victoria, and 1.51 (1.13, 2.03) for B/Yamagata. The GMT ratio (95% confidence interval) for IIV4-HD 60 µg versus IIV4-SD was highest for participants 6 months through < 3 years of age: 4.24 (2.05, 8.76) for A/H1N1, 3.14 (1.53, 6.44) for A/H3N2, 2.04 (1.10, 3.77) for B/Victoria, and 1.92 (1.08, 3.41) for B/Yamagata; similarly, seroneutralization antibody GMT ratio was highest in these participants: 170 (84.6, 340) for A/H1N1, 7.13 (4.90, 10.4) for A/H3N2, 35.8 (22.1, 58.1) for B/Victoria, and 22.7 (14.7, 35.0) for B/Yamagata. This study showed that IIV4-HD (60 µg HA/strain) provides improved immunogenicity without affecting vaccine safety in children.